PENGARUH PENAMBAHAN KARET SILIKON TERHADAP SUDUT KONTAK HIDROPOBIK DAN KARAKTERISTIK ARUS BOCOR PERMUKAAN PADA BAHAN RESIN EPOKSI - Syakur, Abdul; Novia, Ika; Sarjiya, Sarjiya; Tumiran, Tumiran; Berahim, Hamzah (Majalah Ilmiah Teknologi Elektro, 2012)
Currently, polymer materials such as epoxy resin have been used as an insulator in the distribution and transmission line. Some advantages of using this epoxy resin material having the dielectric properties are better than porcelain and glass insulators. On the other side, epoxy resins are also disadvantage the surface is hygroscopic. For the repair was done by adding the surface properties of silicone rubber material This paper describes the effect of adding silicone rubber against contact angle of hidrophobicity and surface leakage current characteristics of epoxy resin materials ( Di-Glycidyl Ether of Bisphenol A (DGEBA) and Methaphenylene-Diamine (MPDA). The study was conducted in the laboratory using the electrode method IEC 587:1984 with NH4Cl contaminants. The voltage applied to the epoxy resin sample at 3.5 kV and 50 Hz frequency The experimental results showed that the addition of silicon rubber in epoxy resin makes the surface material contact angle increases. The higher percentage of silicone rubber, the greater the contact angle and the longer time required for the occurrence of surface discharge.